The Phytochemical screening and antibacterial activity of leaf and fruit extracts of guava (Psidium guajava) - BHARDWAJ, RICHA; NARUKA, DEVYANI (The Indian Journal of Agricultural Sciences, 2023)
An experiment was conducted during 2021–23 at IIS (Deemed to be University) Jaipur, Rajasthan to study the antibacterial efficacy of leaf and fruit extracts of guava (Psidium guajava Linn) and to correlate the activity to the phytochemicals present within these plant parts. The study aims to examine primary and secondary metabolites of the extracts qualitatively and quantitatively. The extracts were then used to check the antibacterial efficacy of these plant parts against four bacteria, of which gram-positive were Bacillus subtilis (MTCC-441) and Staphylococcus aureus (MTCC-737) and gram-negative were Escherichia coli (MTCC-739) and Proteus vulgaris (MTCC-426). The concentration of total phenols and total flavonoids was higher in leaves than in fruits. The activity of methanolic extracts of leaves higher than that of fruits highest activity, was seen against E.coli and lowest activity was seen against S. aureus. No activity was recorded against the aqueous extract of both leaf and fruits.